Do multinational retailers affect the export competitiveness of host countries? - Angela Cheptea (Institut für Angewandte Wirtschaftsforschung (IAW), 2014)
The accelerated overseas expansion of multinational retailers (MRs) over the last decade transformed these companies into major regional and global actors. In this paper we question how MRs arriving in foreign markets affect the export performance of local firms. We develop a theoretical framework that explains the mechanisms by which multinational retailers establishing outlets abroad impact the export performance of local firms and test its predictions empirically for the agri-food sector. The adopted approach draws on recent empirical evidence of the effects of foreign direct investment (FDI) in the retail sector and recent developments in the literature on international trade with heterogeneous firms and on trade and intermediaries. First, incoming multinational retailers may increase the overall export capacity of local firms to any foreign market via an increase in their productivity. The growing competitive pressure in the upstream sector, induced by global retail chains, drives least productive firms out of the market and the average productivity of the sector increases. In addition, retail sector FDI generates productivity gains at the firm level: local suppliers of multinational retailers benefit from the retailers' financial and technological support and become more productive in time. Thus, although the productivity threshold for exporting remains unchanged, some firms reach this threshold and start exporting, while firms above this threshold that experience productivity gains increase their volume of exports ...
Keywords: F12; F14; Q17; F23; 330; multinational retailers; export competitiveness; productivity gains; transnational networks; intermediaries